New records of invasive mammals from the sub-Antarctic Cape Horn Archipelago - Schuttler, Elke; Crego, Ramiro D.; Saavedra-Aracena, Lorena; Silva-Rodriguez, Eduardo A.; Rozzi Marin, Ricardo Roberto; Soto, Nicolas; Jimenez, Jaime E. (My University, 2019)
The southernmost archipelago of the Americas is dominated by invasive mammals that outnumber their native counterparts. Despite the relatively low ability of most invasive mammals to cross cold sea water channels, invaders are apparently colonizing new islands. Our objective was to provide an assessment of the expansion of invasive mammals within these sub-Antarctic ecosystems, determine whether human-mediated movement of invasive species is a plausible dispersal mechanism, and identify areas likely to be colonized in the near future. We report a decade of fieldwork (2006-2017) in 44 sites on 13 islands within the Cape Horn Biosphere Reserve including opportunistic and systematic camera trapping, carnivore diet, questionnaires, small mammal trapping, and walks/transects. We found new records of invasive mammals on seven islands, particularly for American mink (Neovison vison) and American beaver (Castor canadensis). Interviews with fishermen showed that mink, dogs (Canis familiaris), and small rodents are likely passengers in vessels. Finally, species distribution models revealed that the putative invasive-free Cape Horn National Park (55 degrees S) is suitable for several invasive species, suggesting a high risk of invasion if species are introduced. We conclude that it is urgent to implement barriers to dispersal to prevent further invasion. In the case of dogs and cats (Felis catus), the first step should be control actions that target pet owners. Finally, we highlight the need of systematic, long-term biodiversity monitoring and citizen science in the Cape Horn Archipelago and common conservation guidelines for the terrestrial sub-Antarcticecosystems.
Keywords: assisted dispersal; conservation; free-ranging domestic animals; islands; monitoring; range expansion; vertebrates